Comparing DAPSA, DAPSA28, and DAS28-CRP in Patients With Psoriatic Arthritis Initiating a First Tumor Necrosis Factor Inhibitor Across Nine European Countries - Linde, Louise; Georgiadis, Stylianos; Ørnbjerg, Lykke M; Rasmussen, Simon H; Michelsen, Brigitte; Askling, Johan; Di Giuseppe, Daniela; Wallman, Johan K; Závada, Jakub; Pavelka, Karel; Bernardes, Miguel; Matos, Carolina O; et al. (Arthritis care & research, 2024)
OBJECTIVE: Because 66/68 joint counts are not always performed in routine care, we aimed to determine which of the modified 28-joint disease activity index for psoriatic arthritis (DAPSA28) or 28-joint disease activity score with C-reactive protein (DAS28-CRP) should be preferred for monitoring disease activity in psoriatic arthritis (PsA) when the original DAPSA (66/68 joints) is not available. METHODS: Prospectively collected real-world data of European bionaive patients with PsA initiating a first tumor necrosis factor inhibitor were pooled. Remission and response status were evaluated at 6 months by remission (DAPSA ≤ 4, DAPSA28 ≤ 4, and DAS28-CRP < 2.6), response (75% improvement for DAPSA and DAPSA28), and combined EULAR good/moderate responses for DAS28-CRP. Logistic regression analyses on multiple imputed data were used to identify baseline predictors. RESULTS: Remission and response cohorts included 3,159 and 1,866 patients, respectively. The 6-month proportions achieving remission/response were DAPSA (27%/44%), DAPSA28 (28%/44%), and DAS28-CRP (59%/80%). Of 14 possible baseline predictors, 11 predicted both DAPSA and DAPSA28 remission (8 of which also predicted their response, indicated by "*"): longer disease duration*, male sex*, and higher CRP* were positive, whereas older age*, higher body mass index*, patient fatigue*, and global, physician global, health assessment questionnaire score*, and tender and swollen* joint counts were negative predictors. Eight and five of these predicted DAS28-CRP remission and response, respectively. CONCLUSION: In patients with PsA, DAPSA28 should be preferred over DAS28-CRP as a substitute for DAPSA when 66/68 joint counts are not available because of the large overlap in remission and response status and in predictors between DAPSA and DAPSA28.
Keywords: inhibitory TNF; Humans; lidé středního věku; C-reaktivní protein; Arthritis, Psoriatic; antirevmatika; Female; Aged; dospělí; výsledek terapie; senioři; lidé; Biomarkers; Europe; TNF-alfa; Tumor Necrosis Factor Inhibitors; indukce remise; Adult; biologické markery; ženské pohlaví; stupeň závažnosti nemoci; Male; Middle Aged; Treatment Outcome; Remission Induction; Severity of Illness Index; Tumor Necrosis Factor-alpha; psoriatická artritida; mužské pohlaví; prospektivní studie; C-Reactive Protein; Antirheumatic Agents; Evropa; Prospective Studies